Yelling from the sidelines? How German parties employ populist and crisis-related messages on Facebook. Issue 1 (31st December 2022) - Schürmann, Benjamin; Gründl, Johann
ABSTRACT: The possibilities of unfiltered communication in social media provide the perfect opportunity structure for spreading populist ideas. Generally, populist communication features an antagonistic worldview that blames elites for betraying the people and promises to reverse a 'downward societal trend' by bringing the people's 'real' interests back into politics. Although populist success is often attributed to crisis-induced dissatisfaction, research remains unclear on whether and how political actors foster such negative societal perceptions. Building on the German case, our paper accomplishes two things: It explores the use of populist social media communication and relates it to the exploitation of crisis-related messages among political parties. Conducting a manual content analysis of 3, 500 Facebook posts by German parties and leading politicians, we find that the outsider parties AfD and the Left use and combine populist and crisis-related messages by far the most. Insider parties also spread crisis-related content to some extent. However, like the government parties, they are very reluctant to communicate in a populist way. By explaining the communicative output with their relative position in the party system, we deepen the understanding of parties' social media behaviour. Overall, this study offers more in-depth insights into how politicians influence perceptions of the societal state.